A vida se ergue mesmo nas ruínas: os jardins do inumano como paisagem essencial - Renata Villon (e-cadernos ces)
Based on anthropological studies that are critical of the so-called Anthropocene and its impact on the planet and other forms of life, this article, also taking into account the point of view of native peoples, analyses how the concept of inhumanity can be seen as an alternative to the Western regime and the “ruins” that result from its domination. By also bearing in mind the field of animal studies that questions the human superiority over other beings, the present article has its conclusion in the reassertion of the importance of the arts as a way of analysing the inhuman and other possibilities of life, citing certain works by Virginia Woolf and Clarice Lispector as examples.